2019
DOI: 10.1002/chem.201901408
|View full text |Cite
|
Sign up to set email alerts
|

Supported Au Nanoparticles‐Catalyzed Regioselective Dehydrogenative Disilylation of Allenes by Dihydrosilane

Abstract: Supported Au nanoparticles on TiO2 catalyze the unprecedented dehydrogenative disilylation of monosubstituted and 1,1‐disubstituted allenes by Et2SiH2 exclusively on the terminal double bond in a stereoselective manner. Treatment of the disilylation products with H2O, in a one‐pot operation also catalyzed by Au/TiO2, leads to 3‐alkylidene‐1,2,5‐oxadisilolanes, an unknown class of heterocyclic compounds, which are excellent scaffolds for the stereoselective synthesis of alkenes under Hiyama‐type cross‐coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The AuNP-supported TiO 2 (Au/TiO 2 )-catalyzed regioselective dehydrogenative 1,2-desilylation through the one-pot synthesis of novel 3-alkylidene 1,2,5-oxadisilolanes (47) from allenes (46) and diethyl dihydrosilane was reported (Scheme 17). 76 Further, Stratakis et al reported its use in C-C bond forming Hiyamatype reactions for the synthesis of aryl olens. Further, they also reported the catalytic assistance of Au/TiO 2 for the cis-1,2dehydrogenative silylation of alkynes for the synthesis of 2,5dihydro-1,2,5-oxadisiloles (49) (Scheme 18) 77 from alkynes (48a) and dihydrosilanes in benzene at 25 C followed by hydrolysis using water in a one-pot synthesis.…”
Section: Agnp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The AuNP-supported TiO 2 (Au/TiO 2 )-catalyzed regioselective dehydrogenative 1,2-desilylation through the one-pot synthesis of novel 3-alkylidene 1,2,5-oxadisilolanes (47) from allenes (46) and diethyl dihydrosilane was reported (Scheme 17). 76 Further, Stratakis et al reported its use in C-C bond forming Hiyamatype reactions for the synthesis of aryl olens. Further, they also reported the catalytic assistance of Au/TiO 2 for the cis-1,2dehydrogenative silylation of alkynes for the synthesis of 2,5dihydro-1,2,5-oxadisiloles (49) (Scheme 18) 77 from alkynes (48a) and dihydrosilanes in benzene at 25 C followed by hydrolysis using water in a one-pot synthesis.…”
Section: Agnp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Copper-loaded hierarchical mesoporous organic polymer (HMOP) NC-catalyzed Frieldländer annulation for the synthesis of quinolines (78) was achieved from 2-amino benzyl alcohols (76) and aryl ketones (77a) under aerobic conditions (Scheme 28). 90 Further, the same catalyst was used for the synthesis of 3substituted 4-phenyl-1H-1,2,3-triazoles (80a) via the [3 + 2] cycloaddition of sodium azide (66) with substituted phenyl acetylene (3b), followed by nucleophilic substitution with alkyl halides (79a, Scheme 29).…”
Section: Cunp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
“…In an unconventional approach to extend the reactivity of dihydrosilanes, Stratakis further reported the Au(0) NP catalyzed disilylation of mono-substituted and 1,1-disubstituted allenes 6. [16] Dihydrosilane (Et 2 SiH 2 ) was reacted with allenes in presence of nano-Au/TiO 2 (1 mol%) as the catalyst to yield dehydrogenated disilylation adducts 7/8 exclusively on the terminal double bond (Scheme 4).…”
Section: Au/tio 2 Catalyzed Dehydrogenation-di-hydro-disilylationmentioning
confidence: 99%
“…Following the very simple catalytic digermylation protocol of alkynes, we turned our attention to the hydrogermylation of allenes as a new method for the synthesis of vinylgermanes using the readily available Et 3 GeH. Our group has shown some years ago that the analogous Au NP-catalyzed hydrosilylation of allenes is regioselective, with predominant addition on the more substituted double bond, while with dihydrosilanes the main pathway is dehydrogenative disilylation on the terminal double bond . In the literature, there is only one example dealing with the hydrogermylation of allenes .…”
mentioning
confidence: 99%
“…Our group has shown some years ago that the analogous Au NP-catalyzed hydrosilylation of allenes is regioselective, with predominant addition on the more substituted double bond, 17 while with dihydrosilanes the main pathway is dehydrogenative disilylation on the terminal double bond. 18 In the literature, there is only one example dealing with the hydrogermylation of allenes. 19 In this specific report, Ph 3 GeH had been used under catalysis either by Pd(0) or Et 3 B (radical conditions).…”
mentioning
confidence: 99%